MARKETING MARGIN OF LOCALLY PRODUCED MILK COWS IN THE PROVINCE OF BAGHDAD/DISTRICT ABU- GHRAIB FOR PRODUCTIVE SEASON 2015 - & AHMAD, HUSSAN (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research aim to marketing margin account of one kg milk cows to the province of Baghdad district of Abu Ghraib. Collected a sample of (146) producer cow’s milk, (15) broker (milk collector’s) and (21) retailer, random sample selection manner. The average marketing margin of one kg milk cows was about 400 dinars kg, marketing margin retailer and broker were about (250,150) dinar kg respectively, marketing costs of the retailer and broker have amounted to (81.42, 22.02) dinar kg. Retailer and broker profits amounted to about (168.58, 127.98) dinar kg. Dinar per consumer paid all of the producer , retailer and broker was amounted to (46.7, 33.3, 20.0)%, respectively. That causing the decline in broker profits compared to the retailer caused by costs and losses spoiled milk, To the total marketing costs Which caculated for approximately (31%). The results were recommended to using the transfer of milk packed tightly and refrigerated, reduce waste .